2009
DOI: 10.4103/0377-4929.56159
|View full text |Cite
|
Sign up to set email alerts
|

Intraventricular hydatid cyst in a child

Abstract: Hydatid disease is caused by the infestation of the larvae of tapeworms of the genus Echinococcus. The definitive hosts of Echinococcus are various carnivores, the common being the dog. All mammals (more often sheep and cattle) are intermediate hosts. Humans get infected through the feco-oral route by ingestion of food or milk contaminated by dog feces containing ova of the parasite or by direct contact with dogs. The most common sites of infestation are the liver (75%) and lungs (15%). Various authors state a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
19
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 0 publications
0
19
0
1
Order By: Relevance
“…[6] Hydatid cysts typically involve the middle cerebral artery territory, with other less common sites being the skull, cavernous sinus, eyeball, pons, cerebellum, ventricles, and interpeduncular cistern. [15] Cerebral hydatid cysts usually grow slowly and present clinical symptoms when they increase in size and produce a mass effect. This may be due to the elastic structure of the cranial bones,[1617] open sutures, and compressibility of the neural tissue.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[6] Hydatid cysts typically involve the middle cerebral artery territory, with other less common sites being the skull, cavernous sinus, eyeball, pons, cerebellum, ventricles, and interpeduncular cistern. [15] Cerebral hydatid cysts usually grow slowly and present clinical symptoms when they increase in size and produce a mass effect. This may be due to the elastic structure of the cranial bones,[1617] open sutures, and compressibility of the neural tissue.…”
Section: Discussionmentioning
confidence: 99%
“…[131519] A study using cranial CT showed fluid that was generally the same as the CSF without perilesional edema[1]; however, Yis et al . reported perilesional edema,[17] which was also observed by Karak et al ., around the cyst in the presence of active inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The liver and lungs are the common sites of infestation. Cerebral or intraventricular hydatid cysts are rare manifestations, usually encountered in children and young adults 1–4 . They have been reported in patients with patency of the ductus arteriosus 1…”
mentioning
confidence: 99%
“…The incidence of intracranial hydatid disease in India is approximately 0.2% 3 . Diagnosis depends upon the presentation, clinical history with corroborative imaging, serology and operative findings.…”
mentioning
confidence: 99%